UPAYA MENINGKATKAN PRESTASI BELAJAR DENGAN MENERAPKAN MODEL PEMBELAJARAN PAKEM PADA SISWA KELAS V SEMESTER I SDN KRATON 3 TAHUN PELAJARAN 2013/2014 - Dewi Astutik (Widyagogik, 2015)
The success of the learning process in the classroom is largely determined by the learning strategies, however complete and clear other components, without implemented through appropriate strategies, then these components will not have any meaning in the process of achieving goals. Therefore every teacher will teach required to implement certain strategies or methods in the implementation of learning. The purpose of this study are: (a) Want to know the increase in student achievement after the implementation of learning strategies increase the ability to think, (b) Want to know influence student motivation after learning model applied CTL. This study used action research (action research) a total of three rounds. Each round consists of four phases: design, activities and observation, reflection, and refisi. The targets of this research is class V. The data obtained in the form of a formative test results, observation sheet learning activities mengajar.Dari the analyst found that student achievement has increased from cycle I to cycle III, namely, the first cycle (68.00%), cycle II (80.00%), the third cycle (92.00%). Based on these results it can be said that the model of active and creative learning contributes positively to the motivation of students of class V SDN Kraton 3 District of Bangkalan, and this model can be used as an alternative learning.